STRATEGI PERJUANGAN PETANI DALAM MENDAPATKAN AKSES DAN PENGUASAAN ATAS LAHAN - Geidy Tiara Ariendi, Geidy; A. Kinseng, Rilus (Sodality: Jurnal Sosiologi Pedesaan, 2011)
Farmers in Cisarua Village have limited access and land tenure because the land is own by government through plantation concertion (HGU). Those facts lead the farmers for setting strategy to get the access of land cultivate. Generally, this research used qualitative analysis methode which is done since July 2010 to January 2011. Depth interview, direct observation, and questionaire are used to get primary data and literature study is used to get secondary data in this research.  Sample taken as many as thirty four  respondents with the population is Cisarua Society and the frame sample is Cisarua Society who work as farmer. The result of this research shows that Cisarua’s farmer struggle individually by doing compromy with foreman of tea plantation so that they can get access of land tenure.  Strategy choosing that’s used by farmers is influenced by some external and internal factors.